Statistical Analysis of the Short Large‐Amplitude Magnetic Structures: Evolution and Ion Resonance - Shi‐Chen Bai; Ruilong Guo; Quanqi Shi; Anmin Tian; Hui Zhang; Sitian Qin; Alexander W. Degeling (Geophysical Research Letters)
Abstract Short large‐amplitude magnetic structures (SLAMS) play a fundamental role in the formation and energy conversion of the collisionless shock. Nevertheless, the evolution and the ion dynamics inside SLAMS are still unclear. In this study, we performed a superposed analysis of SLAMS near the Earth's bow shock to investigate their properties and internal ion dynamics throughout their evolution. Our results support previously summarized evolutionary trends of SLAMS. Through the wave‐particle interaction, the kinetic energy of solar wind ions is efficiently converted into thermal energy and magnetic field amplification. This interaction gradually transforms the ion distribution within SLAMS, leading to a magnetosheath‐like state upstream of the bow shock inside the SLAMS. The solar wind ion resonance is crucial for the SLAMS development. Our study provides new insights into the formation and energy conversion of the collisionless shock.